Центр як фобія у новелах Тадеуша Ружевича «Гріх» і Тані Малярчук «Родимка» - Венгринюк, Х. (Літературознавчі обрії. Праці молодих учених, 2010)
In this article the stories «The Birthmark» by Tanya Maliarchuk and «The Sin» by Tadeusz Rózewicz are studied from the perspective of «centre as phobia». The centre causes fear; firstly, because it (fear) is alone, it doesn’t have marginal pair, which should attract attention according to the law of marginal / central. In a position «centre as phobia», centre absolutely replaces the margins because it is the only place where a person can run away. That’s why it stays empty.